The Relationship Between Postnatal Mothers' Knowledge of Umbilical Cord Care and the Time of Umbilical Cord Detachment in Babies at the Tamiang Health Center - Sulistiana Sulistiana; Sundari Sundari; Suprapti Suprapti; Surya Ningsih Sitorus; Suhestri Suhestri; Elv. Feedia Mona Saragih (Universitas Malahayati Lampung, 2025)
ABSTRACT Umbilical cord care is an important aspect of newborn care that must be attended to by postnatal mothers, as improper care can lead to serious infections, such as sepsis. This study aims to examine the relationship between postnatal mothers' knowledge of umbilical cord care and the time it takes for the umbilical cord to detach in babies at the Tamiang Hulu Health Center. This study used a quantitative design with a cross-sectional approach and involved 23 postnatal mothers as samples selected through purposive sampling. Data were collected using a questionnaire that assessed the mothers' knowledge of umbilical cord care, as well as observing the time it took for the umbilical cord to detach. The analysis results showed a significant relationship between the mothers' knowledge and the time of umbilical cord detachment, with a p-value of 0.015. Mothers with good knowledge tended to have a faster umbilical cord detachment (less than 7 days), while mothers with limited or insufficient knowledge experienced delays. This study underscores the importance of effective health education regarding umbilical cord care, especially for postnatal mothers, to reduce the risk of infection and accelerate the healing process of the baby's umbilical cord. Keywords : Knowledge, Umbilical Cord Care, Umbilical Cord Detachment Time, Neonates. ABSTRAK Perawatan tali pusat merupakan aspek penting dalam merawat neonatus yang harus diperhatikan oleh ibu nifas. Jika perawatan ini tidak dilakukan dengan benar, risiko infeksi serius seperti sepsis dapat meningkat. Penelitian ini bertujuan untuk menganalisis keterkaitan antara tingkat pengetahuan ibu nifas mengenai perawatan tali pusat dengan durasi pelepasan tali pusat pada bayi di Puskesmas Tamiang Hulu. Penelitian ini menggunakan metode kuantitatif dengan pendekatan cross-sectional. Sebanyak 23 ibu nifas dipilih sebagai sampel melalui teknik purposive sampling. Pengumpulan data dilakukan melalui kuesioner untuk menilai tingkat pengetahuan ibu mengenai perawatan tali pusat, serta observasi waktu lepasnya tali pusat. Hasil analisis menunjukkan adanya hubungan yang signifikan antara pengetahuan ibu dan waktu lepasnya tali pusat, dengan p-value sebesar 0,015. Ibu dengan pengetahuan baik cenderung memiliki waktu lepas tali pusat yang lebih cepat (kurang dari 7 hari), sedangkan ibu dengan pengetahuan kurang atau cukup mengalami keterlambatan. Penelitian ini menggarisbawahi pentingnya edukasi kesehatan yang efektif mengenai perawatan tali pusat, terutama bagi ibu nifas, guna mengurangi risiko infeksi dan mempercepat proses penyembuhan tali pusat bayi. Kata Kunci: Pengetahuan, Perawatan Tali Pusat, Waktu Lepas Tali Pusat, Neonatus.